Dukungan Keluarga untuk Kepatuhan Pengobatan Tuberkulosis Paru - Lahuo, Syahruddin; Tololiu, Kevin Efrain; Haryanto, Joni; Wulansari, Dianis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to investigate family support for compliance with pulmonary tuberculosis treatment. The method used in this research is systematic observation. The research results showed that out of 1,870 articles, 15 articles in this study found that the implementation of family support was not optimal in relation to four important points in family support such as support (informational, instrumental, emotional, and assessment). In conclusion, when the family always provides support in the form of information, emotions, appreciation, and also plays a role for tuberculosis patients, then this encouragement will influence their psychology, so that it will encourage them physically to take medication regularly and adopt a healthy lifestyle as an effort to achieve successful treatment. Apart from that, it is necessary to pay attention to policies, health programs, support for medical and paramedical personnel. Keywords: Family Support, Compliance, Pulmonary Tuberculosis